SOCIAL CAPITAL BUILT UP BY SELF-HELP FAMILY GROUPS - Gvaldaitė, Lijana (Acta Paedagogica Vilnensia, 2010)
The article studies the activity of Italian and Lithuanian self-help family groups based on the social capital perspective. Family self-help as a community phenomenon has a very important helping and educational function for the participants and also contributes to the creation of the welfare of the society. A comparative Italian (Lombardy) and Lithuanian case analysis has been conducted in order to find out what social capital is created for the families themselves and the society in the movement of family self-help. The analysis was based on the interview data (12 interviews) with leaders and participants and data from documents of groups and organizations they belong to. The research demonstrates that the Italian and Lithuanian situation on the social capital for families level is similar: participation in self-help positively modifies family relationship, increases personal maturity and self esteem, helps developing new competences, and finally strengthens and forms the new type of family relationship. Meanwhile the analysis of the social capital for the society has shown that in Lithuania it is being built not as strongly as in Italy due to the fact that the self-help groups in our country are relatively closed, the participants of the groups do not directly get involved in social community activities.
Keywords: self-help family groups; social capital; social relations; social networks; trust; solidarity; family social community activity